Sibawaih Dan Karyanya Al-Kitāb: Tonggak Awal Ilmu Nahwu - Dyah Adila Perdana (CV. SINAR HOWUHOWU, 2026)
Sibawayh was a monumental figure in the history of Arabic linguistics, recognized as the pioneer of Arabic grammar through his monumental work, Al-Kitab. Although he came from a non-Arab background, he succeeded in systematically, scientifically, and comprehensively formulating Arabic grammar, which remains a primary reference in both classical and modern Arabic linguistic studies. This article reviews Sibawayh’s intellectual biography, the background of the composition of Al-Kitāb, the linguistic methods he employed, as well as his influence and intellectual relevance in contemporary language studies. The methods used by Sibawayh demonstrate a scientific approach based on empirical observation, the use of analogy (qiyās), and logical reasoning (ta‘līl) in explaining the structure of the Arabic language. This approach marked an early step in the systematic codification of grammar and became the foundation for the development of Arabic and Islamic linguistics. Al-Kitāb is not merely a normative work, but rather a linguistic encyclopedia containing in-depth discussions ranging from phonology, morphology, syntax, to semantics, organized in an argumentative and dialectical structure. This article also highlights how the methods and theories developed by Sibawayh remain relevant to modern linguistic principles, particularly in aspects of data collection, grammatical function analysis, and scientific reasoning models. Therefore, studying the works and methods of Sibawayh is important not only as a historical legacy, but also as a source of inspiration and conceptual foundation for contemporary linguistic studies. Thus, this research is expected to contribute to a deeper understanding of the classical Arabic linguistic tradition and its relevance to modern language studies.